Research of Clinical and Paraclinical Characteristics of Laryngeal Cancer of National Otorhinolaryngology Hospital of Vietnam from 11/2022 to 4/2023 - Xuan Nghia, Ha; Tuan Son, Nguyen; Dinh Linh, Dao; Thi Nhung, Le; Duc Duy, Pham; Trung Duy, Nguyen (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2023)
Objectives: studying clinical and paraclinical characteristics of laryngeal cancer. Patients and methods: 31 laryngeal cancer patients were diagnosed and treated in the Oncology Department of the national otorhinolaryngology hospital of Vietnam from 11/2022 to 4/2023 by a cross-sectional descriptive study. The results: patients having the most common age range was 60-80 occupied 52.8%, and the mean age was 60.5 ± 9.4, ranging from 35 to 80. Males occupied 97.2% (35/36), females 2.8% (1/36). The most common functional symptom was hoarseness with 94.4%. The mean time of symptom onset was 5.9 ± 6.1, ranging from 1-36 months. The most common tumor site is the vocal cords, accounting for 97.2% of endoscopic and 80.6% of CT SCAN findings. Squamous cell carcinoma accounts for 100%. Tumors in stage I account for 50%. Surgery is the main treatment (75%). Conclusion: Laryngeal cancer is one of the cancers with a high rate in our country. The symptoms are usually non-specific, with hoarseness being the most common symptom. The common form of the disease is squamous cell carcinoma, and surgical treatment at an early stage is the main method.